From making things public to the design of creative democracy: Dewey's democratic vision and participatory design. Issue 2 (2nd April 2020) - Dixon, Brian
ABSTRACT: Participatory design's (PD) shift from the workplace to civic settings has led to a reorientation of the field's political bearings. Informed by science and technology studies, practice is now often framed in terms of design things, infrastructuring, and John Dewey's concept of 'publics'. Taking the publics concept as a starting point, the present article seeks to contribute by providing a broader outline of Dewey's democratic vision. It is proposed that Dewey's vision may be seen to offer a potentially useful perspective that directly relates the 'publics' concept to the areas of freedom, experientialism, and the institutions of government. Linking to contemporary developments in PD and beyond, the vision is seen to carry conceptual and practical implications, which, if borne out, would connect the discipline's capacity to 'spark' publics into being to the processes of policy formation and institutional reform.